2010
DOI: 10.1111/j.1460-2695.2010.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3P-Weibull parameters based on JC and KJC values

Abstract: A B S T R A C T The characterization of fracture toughness of ferritic steels in the ductile-to-brittle transition is problematic due to the scatter of test results. Several proposals using Weibull statistics have been made, some of them in terms of J and others in terms of K; some authors employ a two parameters Weibull function (2P-W), while others use a three parameters function (3P-W), although ASTM E1921 uses 3P-W in terms of K with two fixed parameters to determine the Reference Temperature To. An analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…An analysis about the relationship between Weibull distributions expressed in terms of J and K was presented in reference [7]. It was shown that if the J C results follow a 3P-W, their equivalent K JC values do not exactly fit a 3P-W function obtained by means of a simple transformation of the three parameters.…”
Section: Some Aspects On the Statistical Data Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis about the relationship between Weibull distributions expressed in terms of J and K was presented in reference [7]. It was shown that if the J C results follow a 3P-W, their equivalent K JC values do not exactly fit a 3P-W function obtained by means of a simple transformation of the three parameters.…”
Section: Some Aspects On the Statistical Data Fittingmentioning
confidence: 99%
“…Figure 1 shows the fracture behavior of different materials with temperature, including some that don't have a transition zone. The characterization of fracture resistance of ferritic steels in this region is problematic due to scatter in results, as well as size and temperature dependences [2][3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Substantial research efforts over the last few decades have developed statistical treatments of cleavage fracture based both on macroscopic approaches and on local approaches . The master curve approach has evolved into a standard procedure in characterizing the temperature dependence of the macroscopic fracture toughness over the DBT regime.…”
Section: Introductionmentioning
confidence: 99%
“…Integrity assessments based on such approaches for realistic structural details require a simplified and reliable approach to determine these key material parameters for engineering applications. Substantial research efforts over the last few decades have developed statistical treatments of cleavage fracture based both on macroscopic approaches [11][12][13][14][15] and on local approaches. [16][17][18][19] The master curve approach 7,12,14 has evolved into a standard procedure 20 in characterizing the temperature dependence of the macroscopic fracture toughness over the DBT regime.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness of materials working at the ductile to brittle transition usually shows considerable scatter [1][2][3][4][5][6][7][8] . It is believed that the relative position of the crack tip related to microstructural heterogeneities causes the scatter, this theory is known as the weakest link theory [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%